Persian Archery and Swordsmandship: Historical Martial Arts of Iran, by Manouchehr Moshtagh Khorasani (Revista de Artes Marciales Asiáticas, 2014)
This review covers the book, Persian Archery and Swordsmanship: Historical Martial Arts of Iran by Dr Manouchehr Moshtagh Khorasani. He is the author of several books in this field (Arms and Armor from Iran The Bronze Age to the End of the Qajar Period, 2006; Lexicon of Arms and Armor from Iran: A Study of Symbols and Terminology, 2010) and many important articles. The review looks at the nature of the book, its structure and layout. It discusses the problems inherent in presenting a complex account such as of the martial arts traditions of a region as extensive as the Iranian culture area. The potential audience is explored. A large selection of illustrations relevant to the text is included in the text while an extensive full color catalog is included as section 10.